Survey Etnobotani Tumbuhan Obat pada Masyarakat Dayak Salako di Sekitar Cagar Alam Raya Pasi Provinsi Kalimantan Barat - Irwan Lovadi; Yoga Budihandoko; Niken Wuri Handayani; Dian Setyaningsih; Icuk Setiawan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
The use of plants in traditional medicine has been carried out by indigenous people around the forest on the island of Kalimantan. However, knowledge about the use of plants in traditional medicine by the Salako Dayak community who inhabit the buffer zone of the Raya Pasi Nature Reserve, West Kalimantan Province, has never been documented. This study aims to collect scientific information regarding the use of plants in traditional medicine by the Salako Dayak community in West Kalimantan Province. The research was conducted by conducting semi-structured interviews, and continued with a discussion of 18 respondents who were determined by purposive sampling. The data collected includes: the name of the plant, the part used, the disease/efficacy (medical) of each plant, the method of preparation of medicinal plants, and the dosage/dose rules. In addition, the frequency of citations/mentions (%) of each medicinal plant and the Informant Agreement Factor were also calculated. The results showed that the Salako Dayak community used 85 species of plants in traditional medicine. Piperaceae, Fabaceae, Rubiaceae, and Lamiaceae were the dominant plant families reported by respondents as medicinal plants. In general, the Salako Dayak community mostly uses the roots to be used as medicine, with the method of preparation by boiling or soaking. Callicarpa longifolia is the plant with the highest frequency of citations, and is commonly used to treat: internal fever, ulcers, wounds, abdominal pain, and postpartum medicine at a dose of 3 x 1. In addition, this study also obtained the number of taxa used by the Dayak community. Salako is more diverse in several categories of traditional medicine.